Deterministic and non-deterministic factors affecting the initial data of tasks of optimization-organizational processes - Аrutiunian I.; Kovalenko М. (Ways to Improve Construction Efficiency, 2020)
The article revealed the problem of the need to determine deterministic and non-deterministic factors, depending on the characteristics of each industry, which directly affect the formation of the initial conditions for the tasks of optimization and organizational processes. Determination of determinism and determinants was given. After determining the concept of determinant factors, the main determinant factors in the construction industry were identified that directly affect the preparation of the conditions for the optimization and organizational processes of construction production. The systematization of determinants in the construction industry was carried out according to three types (factors depending on the transportation route; the factor depends on the characteristics of the vehicle, factors directly affecting the transportation time). The factors considered allow solving the problems of optimization and organizational processes in construction using both linear and dynamic programming. After determining the main determinant factors in the construction industry, it becomes necessary to determine uncertainty factors or non-determinant factors in order to draw up initial conditions for optimization and organizational processes that are close to real conditions. A definition of non-determinism and non-determinant factors was given. The main types of non-deterministic factors, such as stochastic, static, interval, fuzzy, are considered. The main non-deterministic factors inherent in the construction industry, namely vehicle breakdowns, are identified; Accidents weather; road conditions over long distances; loading and unloading time; what time is the vehicle at the consumer after unloading; downtime due to non-payment; breakdowns of machines and mechanisms; low-quality materials; delays in subcontracting organizations; delay and dependence on government bodies (act on the opening of construction, bodies of electricity and gas supply networks) adjustments to design and estimate documentation depending on the selected materials or the wishes of the customer. The systematization of non-deterministic factors in the construction industry is carried out depending on their belonging to a certain type. After analyzing the determinate and nondeterministic factors in the construction industry, it was determined that for the formulation of tasks of optimization and organizational processes in construction, dynamic programming of tasks for organizing the provision of construction objects is more suitable.